Relationship between skeletal muscle mass and strength with metabolic syndrome in children - Cao, M Y (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2025)
Objective: To explore the correlation between skeletal muscle mass and strength with metabolic syndrome in children. Methods: This cross-sectional study was conducted involving 383 children aged 10 to 15 years who visited the Department of Child Health Care, Children's Hospital of Nanjing Medical University from June 2021 to December 2022. Their height, weight, waist circumference, body composition, grip strength and blood pressure were measured. Relative skeletal muscle mass, muscle-to-fat ratio, and grip strength-to-body weight index were calculated. The levels of fasting blood glucose, lipids and insulin were tested. Homeostasis model assessment of insulin resistance (HOMA-IR) was calculated. Children were divided into the metabolic syndrome group and the non-metabolic syndrome group. Independent t test or Mann-Whitney U test etc. was used to compare the difference between groups. Spearman correlation analysis and binary Logistic regression were used to investigate the correlation between skeletal muscle mass and strength and metabolic syndrome. The area under the curve (AUC) of receiver operating characteristic (ROC) curve was used to compare the accuracy of the index of skeletal muscle in predicting metabolic syndrome in children. Results: Among the 383 children, 282 (73.6%) were male, at the age of 11.4 (10.6, 12.5) years. There were 216 children (56.4%) diagnosed with obesity and 90 children (23.5%) diagnosed with metabolic syndrome. Relative skeletal muscle mass, muscle-to-fat ratio, and grip strength-to-body weight index of the metabolic syndrome group were all lower than those in the non-metabolic syndrome group (all P<0.001). After adjusting for sex and age, relative skeletal muscle mass, muscle-to-fat ratio, and grip strength-to-body weight index were all negatively correlated with body mass index (r=-0.84, -0.38, -0.63), waist circumference (r=-0.76, -0.36, -0.70), systolic blood pressure (r=-0.42, -0.21, -0.38), diastolic blood pressure (r=-0.33, -0.18, -0.24), triglycerides (r=-0.29, -0.13, -0.23), fasting insulin (r=-0.28, -0.20, -0.29), and HOMA-IR (r=-0.26, -0.18, -0.26) (all P<0.05), and positively correlated with high-density lipoprotein cholesterol (r=0.38, 0.13, 0.31, all P<0.01). After adjusting for sex and age, high relative skeletal muscle mass, high muscle-to-fat ratio, and high grip strength-to-body weight index all decreased the risks of metabolic syndrome (OR=0.80, 0.55, 0.90), obesity (OR=0.53, 0.64, 0.82), hypertension (OR=0.86, 0.58, 0.92), low high-density lipoprotein cholesterol (OR=0.83, 0.62, 0.92), hypertriglyceridemia (OR=0.88, 0.78, 0.96). After adjusting for sex and age, high relative skeletal muscle mass and high grip strength-to-body weight index all decreased the risks of hyperglycemia (OR=0.93 and 0.95, all P<0.05). ROC curve analysis showed that the relative skeletal muscle mass, muscle-to-fat ratio, and grip strength-to-body weight index all had good predictive accuracy of metabolic syndrome in children (AUC=0.79, 0.71, 0.76), with optimal cutoff values of 40%, 1.2, and 35%, respectively. Conclusions: High relative skeletal muscle mass, high muscle-to-fat ratio, and high grip strength-to-body weight index are all protective factors for metabolic syndrome in children. Regular measurement of skeletal muscle mass and grip strength can aid in the early identification and prevention of obesity and metabolic syndrome during childhood